Math, asked by sarika74, 7 months ago

(-36x⁴) ÷(-9x) please explain this​

Answers

Answered by rosepardhi
8

Answer:

4x⁴ aayega iska answer

Answered by brokendreams
0

(-36x⁴) ÷ (-9x) = 4x³

Step-by-step explanation:

Given: Expression (-36x⁴) ÷ (-9x)

To Find: Solution of the given expression

Solution:

  • Solving (-36x⁴) ÷ (-9x)

We have the following expression,

\Rightarrow (-36x^{4}) \ \div \ (-9x)

Dividing it step-by-step, we get,

\Rightarrow \dfrac{-36x^{4}}{-9x}

Eliminating minus sign, we get,

\Rightarrow \dfrac{36x^{4}}{9x}

\Rightarrow \dfrac{(9x)4x^{3}}{9x}

Canceling 9x from numerator and denominator, we get,

\Rightarrow 4x^{3}

Hence, (-36x⁴) ÷ (-9x) = 4x³

Similar questions